Montmorillonite/Poly (L-Lactide) microcomposite spheres as reservoirs of antidepressant drugs and their controlled release property - Shalini Rajkumar; Bhavesh D. Kevadiya; Hari C. Bajaj (Elsevier, 2015)
This work evaluates intercalation of Nortriptyline (NT) and Venlafaxine (VFX) in an interlayer gallery of Na+-MMT (Montmorillonite), which was further compounded with Poly (L-Lactide) (PLLA) to form microcomposite spheres (MPs) for oral controlled drug delivery. The XRD patterns, thermal and spectroscopic analyses indicated intercalation of drugs into the MMT interlayer that was stabilized by electrostatic interaction. No significant changes in structural and functional properties of drugs were found in the MMT layers. In vitro drug release studies showed controlled release pattern.